Dynamics of soil N2O emissions and functional gene abundance in response to biochar application in the presence of earthworms. (1st January 2021) - Wu, Yupeng; Liu, Jiao; Shaaban, Muhammad; Hu, Ronggui
Abstract: Nitrous oxide (N2 O) is a devastating greenhouse gas and acts as an ozone-depleting agent. Earthworms are a potential source of soil N2 O emissions. Application of biochar can mitigate earthworm-induced N2 O emissions. However, the underlying interactive mechanism between earthworms and biochar in soil N2 O emissions is still unclear. A 35-day laboratory experiment was conducted to examine the soil N2 O emission dynamics for four different treatments, earthworm presence with biochar application (EC), earthworm presence without biochar application (E), earthworm absence with biochar application (C) and earthworm absence without biochar application, and the control. Results indicated a negative impact of biochar on earthworm activity, displaying a significantly (p ≤ 0.05) lower survival rate and biomass of earthworms in treatment EC than E. Compared with the control, earthworm presence significantly (p ≤ 0.05) increased cumulative N2 O emissions, while application of biochar in the presence of earthworms significantly (p ≤ 0.05) decreased cumulative N2 O emissions (485 and 690 μg kg −1 for treatments EC and E, respectively). Treatments E and EC significantly (p ≤ 0.05) increased soil microbial biomass carbon (MBC), ammonium (NH4 + -N), nitrate (NO3 − N), and dissolved organic carbon (DOC) content and soil pH as compared with the control. The gene copy number of 16 S rRNA, AOA, AOB, nirS, and nosZ increased for all treatments when compared with the control; however, a significant (p ≤ 0.05) difference among the studied genes was only observed for the nosZ gene (2.05 and 2.56 × 10 6 gene copies g −1 soil for treatments E and EC, respectively). Earthworm-induced soil N2 O emissions were significantly (p ≤ 0.05) reduced by biochar addition. The possible underlying mechanisms may include: (1) short-term negative impacts on earthworm activity; (2) a change of functional gene abundance in earthworm casts; and (3) an increase in soil pH due to addition of biochar. Graphical abstract: Image 1 Highlights: Increased soil N2 O emission by earthworms was significantly reduced by biochar addition. Biochar addition showed a negative impact on earthworm's activity. The copy number of the nosZ gene in cast was increased by biochar addition. Abstract : Earthworm-induced soil N2 O emissions were reduced by biochar application.